Religious Life of Fishermen: Research in Prapag Lor Fishing Village, Losari, Brebes - Miftahudin, Miftahudin; Muhyiddin, Asep (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study investigates the religious life of the fishing community in Kampung Nelayan Prapag Lor, Losari District, Brebes Regency, using a qualitative ethnographic approach. Based on participant observation, in-depth interviews, and documentation analysis, the research reveals that the community’s religious expression is deeply influenced by local culture, socioeconomic conditions, and traditional beliefs. Their religious worldview reflects Clifford Geertz's description of the Abangan variant of Javanese Islam, in which religious practices are not limited to formal worship but are expressed through communal rituals such as slametan, suwuk (protective prayers), and pilgrimage to sacred sites. Religion functions as both a spiritual and social system that provides meaning, structure, and emotional security in a life shaped by uncertainty at sea and limited economic opportunities. While older generations preserve strong ties to tradition, younger members show increasing openness to scriptural and institutional expressions of Islam influenced by education and media. The study argues that religious life in marginalized coastal communities is not a reflection of religious decline, but a creative adaptation to local realities. These findings offer significant insight for scholars of religion, culture, and poverty by highlighting the role of indigenous spirituality in fostering social cohesion and resilience.